Comparison of the assessment of teaching components during distance and traditional learning – perspective of academic teachers and students. Questionnaire survey - Mlodawski, Jakub; Swiercz, Anna; Mlodawska, Marta; Piąta, Aleksandra; Swiercz, Grzegorz; Gawdzik, Barbara (Journal of Education, Health and Sport, 2022)
The Covid-19 pandemic forced students and academic teachers to start distance learning. Although both sides participated in the same process, its assessment from both sides may differ. In our study, using a structured survey, academic teachers and students assessed on a 5-point Likert's scale (where 1 = greater in traditional education, 5 =definitely greater in remote education) the effectiveness of 6 key elements of learning such as: student's involvement (1), student's activity (2), contact with the lecturer (3), consistent manner of work (4), timeliness of tasks performed (5), quality of tasks performed (6) and adequacy of grades awarded (7) . Most of the elements in both groups were assessed as more effective in traditional learning. The average score in the group of teachers in each of the elements was shifted towards greater effectiveness of traditional teaching. The greatest difference in grades between the two groups occurred in the scope of a student's involvement and activity. Students and teachers did not differ in the assessment of contact with the lecturer, although both groups indicated that it was greater in the case of traditional learning. Lecturers and students differed in assessing the effectiveness of key features of learning during distance and traditional education. It is necessary to continuously adapt curricula in order to improve the overall assessment of the examined elements and to ensure that there are no differences between the two groups.